Cell-interactive alginate-chitosan biopolymer systems with tunable mechanics and antibody release rates. (1st November 2017) - Fletcher, Nathan A.; Von Nieda, Evelyn L.; Krebs, Melissa D.
Highlights: Increased polyelectrolyte complex strength without material compositional changes. Increased temperature during gelation increases strength of polyelectrolyte complex. MC3T3 cells respond to increase the gel strength via increased proliferation. Adding CaSO4 to polyelectrolyte complex increases antibody release potential. Glutamate counterions cause increased gel strength with decreasing polymer content. Abstract: This work investigates techniques to produce biocompatible hydrogels with tunable stiffness without the addition of crosslinking agents or altering cell binding sites. Alginate and water-soluble chitosan salts were used to form polyelectrolyte complexes (PECs), where the storage and loss moduli could be increased by raising gelation temperatures. The largest change, a 6.5-fold increase in storage modulus, occurred when the crosslinking temperature was increased from 37 to 50 °C while using chitosan with chlorine counterions. Osteogenic MC3T3 cells were shown to have significantly higher proliferation on the stiffer PECs prepared at 50 °C compared to 37 °C. Gelation temperature showed minimal effect on antibody release, but the inclusion of CaSO4 provided a longer overall release where the rate was nearly linear for several weeks. However, CaSO4 inhibited the strengthening effect of increased gelation temperature. PECs containing glutamate counterions demonstrated an increase in stiffness with decreased chitosan content.